Resolution-defined projections for virtual reality video compression - Dunn, Charles; Knott, Brian (Proceedings of the Workshop on Future Trends of Distributed Computing Systems, 2017)
Spherical data compression methods for Virtual Reality (VR) currently leverage popular rectangular data encoding algorithms. Traditional compression algorithms have massive adoption and hardware support on computers and mobile devices. Efficiently utilizing these two-dimensional compression methods for spherical data necessitates a projection from the three-dimensional surface of a sphere to a two-dimensional rectangle. Any such projection affects the final resolution distribution of the data after decoding. Popular projections used for VR video benefit from mathematical or geometric simplicity, but result in suboptimal resolution distributions. We introduce a method for generating a projection to match a desired resolution function. This method allows for customized projections with smooth, continuous and optimal resolution functions. Compared to commonly used projections, our resolution-defined projections drastically improve compression ratios for any given quality.